ASSESSMENT OF CORROSION BEHAVIOUR OF MACHINED SUPER DUPLEX STAINLESS STEEL OBTAINED WITH THREE DIFFERENT PVD COATED TOOLS - Locks, Edinei (My University, 2019)
Super Duplex Stainless Steels (SDSS) are widely used in offshore oil and gas industrial components. They are dual phase materials consisting of ferrite and austenite in similar ratios with high contents of chromium and presence of molybdenum. This combination of microstructure and chemical composition results in enhanced mechanical strength and corrosion resistance. However, this material has poor machinability, exhibiting the following characteristics: (i) tendency to strain-harden; (ii) extreme adhesive behaviour; and (iii) high cutting temperatures. These circumstances not only result in high tool wear rates, but also lead to poor surface integrity due to the work hardening effect, high roughness and tensile residual stress. To minimize these detrimental effects, PVD coating technologies have been widely applied to cutting tools due to their tribological properties exhibited during cutting, which reduce friction and diminish heat. In this work, three different PVD coatings were tested during the turning of super duplex stainless steel of grade UNS S32750. In addition to the tool performance, surface integrity was assessed by surface texture analysis, residual stresses and hardness profile. The electrochemical behaviour of the machined surface was evaluated by potentiodynamic anodic polarization measurements. Stress cracking corrosion (SCC) tests were also performed. Results indicate a relationship between the tool performance and surface electrochemical behaviour, where the tool with best cutting performance, AlTiN, also presented the best electrochemical behaviour. Stress cracking corrosion was found to be associated with residual stresses on the workpiece, among the three tested PVD coated tools the AlCrN/TiSiN showed lowest tensile residual stresses and lowest SCC susceptibility. The surface generated by AlTiN coated tool presented the highest levels of tensile residual stresses, resulting in a higher SCC susceptibility.
Keywords: Super duplex stainless steel; Machining; Corrosion; PVD coatings